Hydrogen-induced calcite dissolution in Amaltheenton Formation claystones: Implications for underground hydrogen storage caprock integrity. (19th August 2022) - Bensing, Joel P.; Misch, David; Skerbisch, Lukas; Sachsenhofer, Reinhard F.
Abstract: With the rising potential of underground hydrogen storage (UHS) in depleted oil and gas reservoirs or deep saline aquifers, questions remain regarding changes to geological units due to interaction with injected hydrogen. Of particular importance is the integrity of potential caprocks/seals with respect to UHS. The results of this study show significant dissolution of calcite fossil fragments in claystone caprock proxies that were treated with a combination of hydrogen and 10 wt% NaCl brine. This is the first time it has been experimentally observed in claystones. The purpose of this short communication is to document the initial results that indicate the potential alteration of caprocks with injected hydrogen, and to further highlight the need for hydrogen-specific studies of caprocks in areas proposed for UHS. Highlights: Calcite fossils were dissolved in caprock analogues treated with a brine-H2 mixture. Dissolution was not observed in samples treated with dry H2 or brine alone. Calcite dissolution in caprocks for underground hydrogen storage may decrease seal integrity. Caprock specific studies are required for underground hydrogen storage.